Pronomina Bahasa Melayu dalam Film Nujum Pak Belalang Karya Puteh Ramlee - Tahnia, Rahmi; Dahlan, Saidat; Asnawi, Asnawi (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2017)
This research entitled